PTH-141 Gastrointestinal Malignancy – Same Day CT Scanning Post Endoscopy Saves Time Resulting in Earlier MDT Decisions. (17th August 2016) - Lee, HL; Peterson, S; Verma, AM
Abstract : Introduction: Staging CT scanning is essential in guiding the management of patients with newly diagnosed gastrointestinal malignancy when discussed in multi-disciplinary team (MDT) meetings. Long waiting times for staging CT causes delays in MDT decision making for patients and initiating treatment. Kettering General Hospital (KGH) implemented a pathway in December 2014 in which patients with newly detected malignancy on endoscopy can have staging CT scan post endoscopy (same day). We are auditing the effectiveness of this pathway in terms of time saved. Methods: Data was analysed between January 1 st 2014 to December 31 st 2015 from endoscopy, radiology and cancer MDT reporting systems to compare time from day of endoscopy to day of CT and to date of MDT discussion pre and post implementation of the pathway. Patients who underwent endoscopy in December 2014 were excluded, as the pathway was being implemented. Results: There were 90 and 104 patients found to have new possible malignancy on endoscopy in 2014 and 2015 respectively. The median (and mean) days awaiting staging CT and MDT discussion prior to the pathway were 12.5 (11.4) days and 15.0 (16.0) days respectively. Since the implementation of the pathway, median (and mean) days for staging CT was 0 (1.6) days and MDT discussions were 6.0 (7.2) days (p = <0.01). The median days saved waiting for a CT staging and MDT discussion are 12.5 and 9 days. Conclusion: This data shows significant improvement in median time to MDT discussion from endoscopy since the pathway was implemented (15 vs 6 days). The patient pathway implemented by our organisation has helped shortened decision time for MDT outcomes and is highly effective in improving patient care. Patients are diagnosed and staged quickly, requiring fewer visits to the hospital and starting their treatment earlier. We commend this pathway to other endoscopy / radiology departments around the country. Disclosure of Interest: None Declared